Suppression of non-prompt $J/\psi$, prompt $J/\psi$, and Y(1S) in PbPb collisions at $\sqrt{s_{NN}}=2.76$ TeV - CMS collaboration (2256 authors) (2012)
Yields of prompt and non-prompt J/psi, as well as Y(1S) mesons, are measured by the CMS experiment via their dimuon decays in PbPb and pp collisions at sqrt(sNN) = 2.76 TeV for quarkonium rapidity |y|<2.4. Differential cross sections and nuclear modification factors are reported as functions of y and transverse momentum pt, as well as collision centrality. For prompt J/psi with relatively high pt (6.5<pt<30 GeV/c), a strong, centrality-dependent suppression is observed in PbPb collisions, compared to the yield in pp collisions scaled by the number of inelastic nucleon-nucleon collisions. In the same kinematic range, a suppression of non-prompt J/psi, which is sensitive to the in-medium b-quark energy loss, is measured for the first time. Also the low-pt Y(1S) mesons are suppressed in PbPb collisions.